The Influence of Stress Relief, Escapism, Social Influence, and Accessibility Motives on Binge Watching Intensity - Odie Yohandi; Andrine Prima Afneta Arzil (Universitas Sebelas Maret (UNS), 2024)
The discovery of the latest technology, namely the internet, has created increasingly diverse platforms for people to get information and entertainment (new media). One of the entertainment activities that is popular with people today is watching films and serials or dramas from home. Binge watching is a current trend in watching shows, especially among students. This is evidenced by the fact that 90% of the young generation aged 20-33 years have binge watched, and the age group that binge watches most often are those at university or student level. One of the favorite online streaming services is Netflix. Seeing this phenomenon, researchers wanted to know which motives influenced the intensity of students' binge watching This research uses an explanatory quantitative analysis method and was conducted at Universitas Sebelas Maret. Population chosen in this research is 46.227 active students in Universitas Sebelas Maret. The Slovin formula was used in determining the sample which resulted in a sample of 99 active students and distributed equally to the 4 selected faculties. The following principal research conclusions are drawn from this study, which examines the relationship between the Intensity of Binge Watching on Netflix and the Motives for Binge Watching on Netflix: (1) Stress Relief Motive has a positive and significant effect on Binge Watching Intensity on Netflix; (2) Escapism Motive has no significant effect on Binge Watching Intensity on Netflix; (3) Social Influence Motive has a positive and significant effect on Binge Watching Intensity on Netflix; (4) Accessibility Motive has a positive and significant effect on Binge Watching Intensity on Netflix.